Location-Based Services (LBS): An emerging innovative transport service technology and a research agenda - Tschangho John Kim (European Regional Science Association (ERSA), 2002)
There are many players in business for the location-based services (LBS). There are thin clients, usually mobile, and thick clients. From the service provider's side, there are companies such as Nokia and Motorola providing hardware; there are Microsoft and Oracle providing software tools, and proxy and brokers providing 'responses' to users 'requests'. In many cities in the World, the travel cost function based on the fixed distance unit cost would not provide accurate cost figures to users. Frequently, we found it is much faster to get to a point in a city by taking longer belt parkway routes rather than taking shorter city streets. In addition, certainly during peak hours in all cities and most of time during the day in major metropolitan areas in the World, the congestion factor has to be included in calculating cost functions. One of the biggest challenges that transportation planners and engineers face these days is to provide current and future road/traffic conditions based on real time data. Obtaining real time data and providing the current road/traffic conditions in many cities in the World is no longer an issue due to the availability of beacon, GPS, loop detectors and video cameras. Recently, personal communication systems (PCS) may provide a role as a medium for collecting inexpensive real time traffic data. The following are few sample issues we need to explore for providing bases for agents that are willing to provide efficient and accurate location-based services: 1. Efficient Means to incorporate real time data in a cost function for providing the best routes to users, 2. How to guide users in dynamically changing road/traffic conditions, 3. Formulating operational Functional Forms for Estimating Routing Costs, 4. Development of Efficient and Accurate Solution Algorithms, 5.Development of Interoperable LBS systems among North American, European, and Asian countries.
Keywords: 330